RADIOISOTOPES AND RADIOPHARMACEUTICALS IN NUCLEAR CARDIOLOGY - Tamat, Swasono R. (Jurnal Radioisotop dan Radiofarmaka, 2001)
RADIOISOTOPES AND RADIOPHARMACEUTICALS IN NUCLEAR CARDIOLOGY. Nuclear medicine studies of the heart represent one of the fastest growing areas of research and clinical interest. Some years ago, nuclear medicine cardiac studies were limited to evaluations of myocardial infarction. Developments in radiopharmaceutical chemistry and instrumentation have made possible advances in cardiovascular nuclear medicine. Techniques and radiopharmaceuticals now exist for the imaging of viable myocardium and the determination of myocardial tissue metabolism, as well as radionuclide angiography to obtain quantitative information of cardiac output, mean transit times, cardiac volumes, and ejection fractions. This paper will firstly describe the anatomy and physiology of the heart as to relate to the radiopharmaceuticals which will be discussed, and will secondly explore various radiopharmaceuticals which have been used for various purposes in cardiac imaging, then will explore radioisotopes which have been proposed for myocardial treatment. RADIOISOTOP DAN RADIOFARMAKA DI BIDANG KARDIOLOGI NUKLIR. Studi jantung secara kedokteran nuklir merupakan salah satu bidang penyidikan dan minat klinis yang paling cepat berkembang. Beberapa tahun lalu, studi jantung secara kedokteran nuklir terbatas pada evaluasi infark jantung. Perkembangan di bidang kimia-radiofarmaka dan instrumentasi telah mendorong kemajuan di bidang kedokteran nuklir kardiovaskular. Teknik-teknik dan radiofarmaka sekarang telah tersedia untuk penyidikan jaringan jantung yang masih hidup dan penentuan metabolisme jaringan jantung, dan juga angiografi radionuklida untuk memperoleh informasi kuantitatif mengenai luaran jantung, waktu transit rataÂ rata, volume jantung, dan fraksi ejeksi. Makalah ini pertama akan menerangkan anatomi dan fisiologi jantung dalam kaitannya dengan radiofarmaka yang akan dibahas, dan kemudian akan meninjau berbagai radiofarmaka yang telah digunakan untuk berbagai keperluan penyidikan jantung, dan kemudian meninjau radioisotop yang telah diusulkan untuk penanganan masalah jantung.